Tube shelters from agricultural plastic waste: An example of circular economy. (20th September 2020) - Martínez Urreaga, J.; Beltrán, F.R.; Acosta, J.; Aguinaco, T.; Fonseca, C.; Ochoa, A.; Oliet Palá, J.A.; González-Sánchez, C.; de la Orden, M.U.
Abstract: The use of recycled plastics in applications similar to those of the original plastic is of great interest for the fulfillment of the circular economy policies objectives. In this work, the feasibility of using recycled agricultural plastics in the manufacture of tube shelters for plant seedlings, which can be used in forest restoration and other plantations, has been investigated. The recycled plastics and their blends with a virgin polyethylene were characterized using spectroscopic techniques and thermal analysis. The effects of the recycled plastics on the optical and mechanical properties of the blends, which are key properties in the selection of materials for tube shelters, were measured using UV–Vis spectroscopy and tensile testing. Thermal stability and degradation during an accelerated aging test were also investigated. The use of recycled plastics did not alter the stability of the blends, but there were decreases in elongation at break and UV and blue light transmission, with small decreases in red light transmission and without significant changes in the red-far red ratio. Blends with less than 50 wt% of recycled plastics show only small decreases in the elongation and provide an adequate light transmission for seedlings. Therefore, the results indicate that significant amounts of recycled agricultural plastics can be used in the manufacture of tube shelters, with both economic and environmental advantages. Graphical abstract: Image 1 Highlights: Tube shelters for seedlings were obtained from recycled agricultural plastics. Tubes obtained from recycled plastics show good mechanical and thermal properties. Recycled plastics block UV radiation and reduce blue light transmission. Red light transmission, critical for seedling growth, is only slightly reduced. Significant amounts of recycled agricultural plastics can be used in this application.